2022
DOI: 10.1021/acsami.2c00340
|View full text |Cite
|
Sign up to set email alerts
|

High Entropy Oxide Relaxor Ferroelectrics

Abstract: Relaxor ferrolectrics are important in technological applications due to a strong electromechanical response, energy storage capacity, electrocaloric effect, and pyroelectric energy conversion properties. Current efforts to discover and design new materials in this class generally rely on substitutional doping of known ferroelectrics, as slight changes to local compositional order can significantly affect the Curie temperature, morphotropic phase boundary, and electromechanical responses. In this work, we demo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…The first studies in this area are already showing promising results with thin films of the perovskite Ba­(Ti,Sn,Zr,Hf,Nb)­O 3 exhibiting relaxor behavior in its dielectric properties. Transmission electron microscopy has shown that the cation distortion in this material occurs collectively over a few unit cells in polar nanodomains, suggesting that not just Ti but the other d 0 elements are also participating in the behavior Point defects including vacancies : Given the profound level of configurational disorder in HEOs, more conventional forms of disorder in these materials have remained relatively unexplored.…”
Section: Entropy Enhancements Due To the Local Environmentmentioning
confidence: 99%
“…The first studies in this area are already showing promising results with thin films of the perovskite Ba­(Ti,Sn,Zr,Hf,Nb)­O 3 exhibiting relaxor behavior in its dielectric properties. Transmission electron microscopy has shown that the cation distortion in this material occurs collectively over a few unit cells in polar nanodomains, suggesting that not just Ti but the other d 0 elements are also participating in the behavior Point defects including vacancies : Given the profound level of configurational disorder in HEOs, more conventional forms of disorder in these materials have remained relatively unexplored.…”
Section: Entropy Enhancements Due To the Local Environmentmentioning
confidence: 99%
“…The first studies in this area are already showing promising results with thin films of the perovskite Ba(Ti,Sn,Zr,Hf,Nb)O 3 exhibiting relaxor behavior in its dielectric properties. Transmission electron microscopy has shown that the cation distortion in this material occurs collectively over a few unit cells in polar nanodomains, suggesting that not just Ti but the other d 0 elements are also participating in the behavior [45].…”
Section: Entropy Enhancements Due To the Local Environmentmentioning
confidence: 92%
“…Interest in perovskite HEOs escalated. HEO perovskites showed indications of relaxor ferroelectricity 84–87 . Son et al.…”
Section: Historical Perspectivementioning
confidence: 99%